Japanese-trained armies in Southeast Asia - Lebra, Joyce 1925-2021 (ISEAS, 2010)
This is the first study by a Western scholar of a significant facet of the history of the Second World War - Japanese-trained independence and volunteer armies as agents of revolution and modernization.